2015
DOI: 10.1038/mp.2015.57
|View full text |Cite|
|
Sign up to set email alerts
|

Gene expression in major depressive disorder

Abstract: The search for genetic variants underlying major depressive disorder (MDD) has not yet provided firm leads to its underlying molecular biology. A complementary approach is to study gene expression in relation to MDD. We measured gene expression in peripheral blood from 1848 subjects from The Netherlands Study of Depression and Anxiety. Subjects were divided into current MDD (N=882), remitted MDD (N=635) and control (N=331) groups. MDD status and gene expression were measured again 2 years later in 414 subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(147 citation statements)
references
References 64 publications
10
134
1
2
Order By: Relevance
“…Furthermore, one meta-analysis of longitudinal studies reported a modest effect of IL-6 levels on the risk of developing subsequent depressive symptoms (Valkanova et al 2013). A pathway analysis on transcriptomic data showed that genes upregulated in MDD subjects com-pared to controls were enriched in IL-6 signalling path-ways (Jansen et al 2016). …”
Section: Peripheral Biomarkersmentioning
confidence: 99%
“…Furthermore, one meta-analysis of longitudinal studies reported a modest effect of IL-6 levels on the risk of developing subsequent depressive symptoms (Valkanova et al 2013). A pathway analysis on transcriptomic data showed that genes upregulated in MDD subjects com-pared to controls were enriched in IL-6 signalling path-ways (Jansen et al 2016). …”
Section: Peripheral Biomarkersmentioning
confidence: 99%
“…DCTN1 gene variants can also cause distal motor neuronopathy type VIIB and confer increased susceptibility to amyotrophic lateral sclerosis [33][34]. Many other genes may be involved in the pathogenesis of depression [35,36] (Table 1). New players, such as epigenetic changes, alterations in mtDNA related to oxidative stress, and modifications in telomere length may also contribute to alter neuronal mechanisms involved in depressive conditions [37].…”
Section: Pathogenic Genesmentioning
confidence: 99%
“…Genetic factors account for around 22% of the variation in gene expression between individuals, with the remaining variation due to environmental and stochastic factors (127)(128)(129). The genome-wide analysis of gene expression, known as transcriptomics, has identified genes and molecular processes underlying a range of brain-related traits (14,130,131) and informed the development of gene expression panels for the classification and diagnosis of disease (132)(133)(134).…”
Section: Mapping Complex Traits With Genome-wide Gene Expression Datamentioning
confidence: 99%
“…Experiment-wide differences in blood gene expression between phenotypically affected cases and controls have been reported for many neurological disorders, including stroke (251-253), multiple sclerosis (254,255), and Alzheimer's disease (256)(257)(258), as well as neuropsychiatric disease such as schizophrenia (259-261) and major depressive disorder (14). Of particular interest, the study of major depression found blood gene expression could not only separate depressed and non-depressed individuals, but depressed individuals from those with remitted depression.…”
Section: Peripheral Gene Expression In Migrainementioning
confidence: 99%
See 1 more Smart Citation